2012
DOI: 10.3727/096368912x640457
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Paracrine Effects of Human Cord Blood Cells on Damaged Neocortex in an Animal Model of Cerebral Palsy

Abstract: Neonatal asphyxia is an important contributor to cerebral palsy (CP), for which there is no effective treatment to date. The administration of human cord blood cells (hUCBCs) is emerging as a therapeutic strategy for the treatment of neurological disorders. However, there are few studies on the application of hUCBCs to the treatment of neonatal ischemia as a model of CP. Experiments and behavioral tests (mainly motor tests) performed on neonatal hypoxia/ischemia have been limited to short-term effects of hUCBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 64 publications
0
51
0
1
Order By: Relevance
“…The large variation in infarct size makes the small morphological changes undetectable. Several studies on neonatal HIE have reported the beneficial effects of cell therapies in behavioral tests without any morphological improvement [11,36,37]. Such reports show that the lack of morphological improvement does not preclude an improvement in behavior.…”
Section: Discussionmentioning
confidence: 97%
“…The large variation in infarct size makes the small morphological changes undetectable. Several studies on neonatal HIE have reported the beneficial effects of cell therapies in behavioral tests without any morphological improvement [11,36,37]. Such reports show that the lack of morphological improvement does not preclude an improvement in behavior.…”
Section: Discussionmentioning
confidence: 97%
“…Both UCB cells and cells derived as a result of their differentiation in vitro produce various neurotrophic factors, such as brain-derived neurotrophic factor, glialderived neurotrophic factor and neurotrophins 3 and 4-5 [9,10]. Additionally, UCB cells secrete an array of biologically active compounds (GRO-a, MIP-1a, MCP-1, MCP-3, RANTES, SDF-1, G-CSF, GM-CSF, interleukins [IL]-6 and -8) with neuroprotective, immunomodulating, anti-apoptotic and anti-inflammatory activities [11]. Presumably, paracrine regulation, including neuroprotection and stimulation of neurogenesis in the brain, is the major mechanism responsible for the therapeutic effect of systemic administration of UCB cells [12,42].…”
Section: Discussionmentioning
confidence: 99%
“…By producing neurotrophic factors, these cells may contribute to the regeneration of the central nervous system as regulators of neuronal and glial activity [11]. Both UCB cells and cells derived as a result of their differentiation in vitro produce various neurotrophic factors, such as brain-derived neurotrophic factor, glialderived neurotrophic factor and neurotrophins 3 and 4-5 [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation would thereby be reduced in brain [33]. Bae et al [34] agreed that paracrine influences were the primary influence on intrinsic cell survival. Human umbilical cord blood cells reduced upregulation of CX43 and thereby brought about attenuation of reactive gliosis [35].…”
Section: Mechanism Of Action Of Stem Cells In Acute Studiesmentioning
confidence: 99%